Circulating microRNAs in heart failure with reduced and preserved left ventricular ejection fraction. (23rd January 2015) - Wong, Lee Lee; Armugam, Arunmozhiarasi; Sepramaniam, Sugunavathi; Karolina, Dwi Setyowati; Lim, Kai Ying; Lim, Jia Yuen; Chong, Jenny P. C.; Ng, Jessica Y. X.; Chen, Yei‐Tsung; Chan, Michelle M. Y.; Chen, Zhaojin; Yeo, Poh Shuan D.; et al.
Abstract Aim The potential diagnostic utility of circulating microRNAs in heart failure (HF) or in distinguishing HF with reduced vs. preserved left ventricular ejection fraction (HFREF and HFPEF, respectively) is unclear. We sought to identify microRNAs suitable for diagnosis of HF and for distinguishing both HFREF and HFPEF from non‐HF controls and HFREF from HFPEF. Methods and results MicroRNA profiling performed on whole blood and corresponding plasma samples of 28 controls, 39 HFREF and 19 HFPEF identified 344 microRNAs to be dysregulated among the three groups. Further analysis using an independent cohort of 30 controls, 30 HFREF and 30 HFPEF, presented 12 microRNAs with diagnostic potential for one or both HF phenotypes. Of these, miR‐1233, ‐183‐3p, ‐190a, ‐193b‐3p, ‐193b‐5p, ‐211‐5p, ‐494, and ‐671‐5p distinguished HF from controls. Altered levels of miR‐125a‐5p, ‐183‐3p, ‐193b‐3p, ‐211‐5p, ‐494, ‐638, and ‐671‐5p were found in HFREF while levels of miR‐1233, ‐183‐3p, ‐190a, ‐193b‐3p, ‐193b‐5p, and ‐545‐5p distinguished HFPEF from controls. Four microRNAs (miR‐125a‐5p, ‐190a, ‐550a‐5p, and ‐638) distinguished HFREF from HFPEF. Selective microRNA panels showed stronger discriminative power than N‐terminal pro‐brain natriuretic peptide (NT‐proBNP). In addition, individual or multiple microRNAs used in combination with NT‐proBNP increased NT‐proBNP's discriminative performance, achieving perfect intergroup distinction. Pathway analysis revealed that the altered microRNAs expression was associated with several mechanisms of potential significance in HF. Conclusions We report specific microRNAs as potential biomarkers in distinguishing HF from non‐HF controls and in differentiating between HFREF and HFPEF.